Analysis of the Community Satisfaction Survey at the Medan City Investment and One Stop Integrated Licensing Service in 2020 (DPMPPTSP) - Rio Ariangga Hutagalung; Wahyu Syarvina (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2022)
The calculation of the community satisfaction index is carried out by the relevant agencies on a regular basis to determine the progress of the unit's performance in the services of government agencies, which can be used as a separate policy material to further improve the quality of service. . Public. Service At the same time, the aim of this study is to measure SMI's satisfaction with its customers, to understand what needs to be improved and how to increase people's satisfaction. PermenpanRB No. 14 of 2017 Indicators of Community Satisfaction Measurement are System Requirements, Mechanisms and Procedures, Completion Time, Costs/Tariffs, Product Specifications by Type of Service, Implementation Capacity, Implementation Behavior, Facilities and Infrastructure, and Complaints, Advice and Feedback Handling. In addition, this study aims to find out how satisfied SMIs are with their customers and what can be done to make them more satisfied. The Community Satisfaction Index (IKM) based on the One Stop Integrated Service and Investment Indicator (DPMPTSP) Medan takes into account factors such as system requirements, mechanisms and procedures. Community Satisfaction (SKM) is 80.43 with a range of 76.61-88.30. The results are still among the good grades. The service elements that are considered the most satisfactory are cost/task points and complaint handling with an average of 3.6, while the lowest points are service hours and permit issuance procedures, with an average of 2.85.